The Ideas of José Ortega y Gasset and Critique of the Ukrainian Populism in Oksana Zabuzhko’s Book Notre Dame D’Ukraine - Pronkevich, Oleksandr (Populismo y propaganda: entre el presente y el pasado, 2020)
The paper studies reception of philosophical ideas of José Ortega y Gasset in the book Notre D’Ukraine: Ukrainka in the Conflict of Mythologies written by Oksana Zabuzhko. The Ukrainian author uses the Spanish thinker’s theories about rebellion of the masses and crisis of elites to reinterpret the biography of Lesya Ukrainka, the central figure of the Ukrainian national literary canon, and to create a powerful document of the intellectual propaganda aimed at populism.